Dissolved radioelements in (oil) water wells in Parana basin, Brazil - Bonotto, Daniel Marcos [UNESP] (A A Balkema Publishers, 2001)
This paper describes the results of a study on groundwaters from Tubarao Group at the Parana sedimentary basin, São Paulo State, Brazil. The purpose of this study was to integrate chemical and U-isotopes data in order to evaluate the models for quantifying different relative volumes of mixing waters in a resultant water. Despite it was possible to generate a typical triangle involving U-238 and its daughter U-234, the U-isotopes model failed to interpret the major hydrochemical facies observed in the studied localities.